MAPPING THE DIASPORIC EXPERIENCE IN THE NAMESAKE - Jaiswal, Ankit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In an increasingly globalised world, transnational migrations are not just movements across borders but also transitions across languages, cultures, and identities. The condition of being “in-between”—of being neither fully here nor there—produces a persistent sense of otherness. Lahiri’s protagonists often inhabit these in-between zones, where they are required to reconcile inherited cultural legacies with adopted environments. This study investigates how Lahiri’s characters experience and internalise displacement, negotiate cultural dislocation, and construct fractured yet meaningful identities within diasporic spaces.